2008
DOI: 10.1101/gr.7101908
|View full text |Cite
|
Sign up to set email alerts
|

Bird-like sex chromosomes of platypus imply recent origin of mammal sex chromosomes

Abstract: In therian mammals (placentals and marsupials), sex is determined by an XX female: XY male system, in which a gene (SRY) on the Y affects male determination. There is no equivalent in other amniotes, although some taxa (notably birds and snakes) have differentiated sex chromosomes. Birds have a ZW female: ZZ male system with no homology with mammal sex chromosomes, in which dosage of a Z-borne gene (possibly DMRT1) affects male determination. As the most basal mammal group, the egg-laying monotremes are ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
260
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(270 citation statements)
references
References 41 publications
(59 reference statements)
7
260
2
1
Order By: Relevance
“…Mapping the genes on the five X and five Y chromosomes confirmed that platypus sex chromosomes have no homology to the therian X. But, surprisingly, they have extensive homology to the bird ZW sex chromosome pair 52.…”
Section: Platypus Sex Chromosomes Rewrote Mammal Chromosome Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping the genes on the five X and five Y chromosomes confirmed that platypus sex chromosomes have no homology to the therian X. But, surprisingly, they have extensive homology to the bird ZW sex chromosome pair 52.…”
Section: Platypus Sex Chromosomes Rewrote Mammal Chromosome Evolutionmentioning
confidence: 99%
“…Sequence comparisons between X‐Y shared genes revealed that the large X 5 and tiny Y 5 that terminate the chain are the most diverged, and therefore the oldest members of the chain 54, suggesting that they represent the original mammalian sex chromosomes. X 5 is largely homologous to the bird Z 52.…”
Section: Platypus Sex Chromosomes Rewrote Mammal Chromosome Evolutionmentioning
confidence: 99%
“…Surprisingly, it was found that none of the platypus X chromosomes share homology with the therian X chromosome (Veyrunes et al, 2008). Instead, the conserved region of the therian X chromosome is homologous to platypus chromosome 6 (Veyrunes et al, 2008), whereas the added region of the eutherian sex chromosomes is orthologous to parts of chromosomes 15q and 18p (Veyrunes et al, 2008) (Figure 2). The observation that therian X chromosome is represented by an autosome in monotremes unambiguously dates the origin of the therian sex chromsomes to after the divergence of monotermes from therians (166 MYA), but before the therian radiation (148 MYA).…”
Section: Marsupial Sex Chromosomesmentioning
confidence: 99%
“…In general, regions with suppressed or no recombination tend to accumulate repetitive DNA sequences (for review see Charlesworth et al, 1994;Gvozdev et al, 2005). Nonrecombining parts of the Y chromosome have accumulated repetitive DNA, particularly in the mammalian (Erlandsson et al, 2000;Skaletsky et al, 2003) and Drosophila melanogaster (Pimpinelli et al, 1995) Y chromosomes, which are evolutionarily ancient, originating before 165 and 60 mya, respectively (Graves, 2005;Veyrunes et al, 2008). However, the process of accumulation of repetitive sequences is apparent even in evolutionarily young sex chromosomes, such as in Drosophila miranda (Steinemann and Steinemann, 1992), Silene latifolia (Hobza et al, 2006;Kejnovsky et al, 2006a) or Carica papaya (Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%